2013
DOI: 10.1507/endocrj.ej12-0263
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a free radical scavenger in the ovarian follicle [Review]

Abstract: This review summarizes new findings related to beneficial effects of melatonin (N-acetyl-5-methoxytryptamine) on reproductive physiology. Recently many researchers have begun to study the local role of melatonin as an antioxidant. We focused on intra-follicular role of melatonin in the ovary. Melatonin, secreted by the pineal gland, is taken up into the follicular fluid from the blood. Reactive oxygen species (ROS) are produced within the follicles, during the ovulatory process. Melatonin reduces oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
141
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 130 publications
5
141
0
12
Order By: Relevance
“…Melatonin is a powerful free radical scavenger and a broad-spectrum antioxidant [31,32]. We previously demonstrated that melatonin is present in human ovarian follicles and that its concentration increases during follicular growth [18][19][20]. We also reported that melatonin is taken up into the follicular fluid from the blood, and that it protects oocytes from ROS within the follicle during ovulation Figure 1 Tumor necrosis factor alpha (TNFα) concentrations in follicular fluids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin is a powerful free radical scavenger and a broad-spectrum antioxidant [31,32]. We previously demonstrated that melatonin is present in human ovarian follicles and that its concentration increases during follicular growth [18][19][20]. We also reported that melatonin is taken up into the follicular fluid from the blood, and that it protects oocytes from ROS within the follicle during ovulation Figure 1 Tumor necrosis factor alpha (TNFα) concentrations in follicular fluids.…”
Section: Discussionmentioning
confidence: 99%
“…[ [18][19][20]33]. Reduced oxidative stress and increased antioxidant activities by melatonin in follicular fluids by ultralong GnRHa therapy may also have contributed to the improvement of implantation rate and pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant properties of melatonin have been extensively studied , Tamura et al 2013. The scavenger activity of melatonin or of its metabolites may thus account for its beneficial effect on follicular and oocyte development (Tamura et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Система окислителей и антиоксидантов присут-ствует и в яичнике, участвуя в процессах роста и со-зревания яйцеклеток [20]. Количество образующих-ся свободных радикалов тщательно контролируется для поддержания окислительно-восстановительного гомеостаза.…”
unclassified